School Without Classroom: An Experimental Study Of The Horizontal Education Model In An Alternative Learning Community - Amalia Tasya (Journal of Pedagogi, 2025)
This study aims to explore the effectiveness of the horizontal education model in alternative learning communities, focusing on the implementation of the "classless school" concept at Sanggar Anak Alam (SALAM) Yogyakarta. Traditional education systems that tend to be hierarchical and rely on memorization as the primary method often neglect active student engagement and the development of critical skills. As an alternative, the horizontal education model offers a more flexible and inclusive approach by emphasizing equality between teachers and students, project-based learning, and cross-age collaboration. This study used a quasi-experimental design with a quantitative approach and a pre-test post-test control group method. The results showed that the horizontal education model significantly improved students' academic achievement, creativity, collaboration, learning independence, and learning satisfaction. These findings provide empirical evidence supporting the transition to a more student-centered education system that is relevant to the challenges of the modern world. This education model has the potential to be adapted in the context of global education to create a more inclusive, progressive, and sustainable learning environment.